ChemInform Abstract: Challenges in Reduction of Dinitrogen by Proton and Electron Transfer. Issue 38 (10th September 2014) - van der Ham, Cornelis J. M.; Koper, Marc T. M.; Hetterscheid, Dennis G. H.
Abstract Review: reaction mechanisms of a dissociative, an alternating associative, and a distal associative pathway, 50 refs.